TRIDIMENSIONAL (3D) MODELING OF TRUNKS AND COMMERCIAL LOGS OF Tectona grandis L.f. - Schirmbeck Chaves, Arthur Guilherme; Sanquetta, Carlos Roberto; Arce, Júlio Eduardo; dos Santos, Luiz Orlando; Moreira, Iuri Maicon; Miguel Franco, Fernanda (Floresta, 2018)
The development and application of technological innovations have been some of the main focuses of the productive sectors. One technological innovation that has been gaining prominence is the three-dimensional modeling (3D) of inventory and forest planning activities. In this study, it was possible to assess the accuracy of three-dimensional scanning of trunks of Tectona grandis L.f. by digital photogrammetry by using photos taken with a smartphone. The study was carried out in a Teak plantation of 46.54 ha. Systematic sampling by plots was used. Based on the diametric distribution of the stand, thirty trees were selected for the three-dimensional scanning procedure by the Close to Range technique. After three-dimensional scanning, each tree was scaled by the Smalian method and sectioned into 2.35 meters long logs for assessment using the xylometer method. The thirty trees resulted in 121 logs that had their volumes measured using the xylometer. Using three-dimensional modeling, it was possible to model and measure the volume of 71 logs in classes A (0.10 to 2.45), B (2.45 to 4.80), and C (4.80 to 7.15). The trunk of the trees could not be modeled for all trees at the highest heights because of the quality of the cloud of data points. Records that could not be entirely modeled (2.35 meters) were ignored. The cubing methods were compared by the paired t-test. Therefore, it was possible to model lower logs (0.10 m to 2.45 m) more accurately than by using the traditional Smalian method, with a one-meter interval between sections.